SHARIA TALENT IN IMPROVING THE PERFORMANCE OF SHARIA FINANCIAL INSTITUTIONS - Helza Sabila, Rani; Abadiyah, Rifdah; Sumartik, Sumartik (JURNAL EKBIS, 2024)
Employee performance is an important factor in an organization's ability to succeed and survive. The extent to which individuals or groups succeed in achieving goals and have a positive impact on organizational results is reflected in employee performance. Apart from ensuring compliance with sharia principles, sharia talent plays an important role in growing added value, fostering customer trust, and ensuring the survival of Bank KCP Sidoarjo as a sharia banking organization. Apart from directly assisting Bank BSI KCP Sidoarjo operations in navigating the nuances of the sharia banking sector, training is very important to improve individual employee performance. As a sharia banking institution, the performance and sustainability of Bank BSI KCP Sidoarjo is greatly influenced by employee engagement. Investing strategically in increasing employee engagement can help Bank BSI KCP Sidoarjo achieve long-term growth and success. With employee engagement as an intervening variable, the aim of this research is to determine the influence of sharia talent and training on the performance of BSI KCP Sidoarjo bank employees. This research is quantitative research with SEM-PLS as a data analysis method with Smart PLS tools.4. Consisting of 100 research sample respondents. The research results show that talent sharing, training and employee engagement have a positive and significant influence on employee performance. Furthermore, talent sharing and training have a positive and significant influence on improving the performance of Bank BSI KCP Sidoarjo employees through employee engagement.